Museums as Intersectional Spaces for Artivist Solidarity - Haapalainen, Riikka; Suominen, Anniina; Pusa, Tiina; Järvinen, Jasmin; Orenius, Melanie (Intellect, 2024)
This chapter responds to the themes of pedagogical sensibilities and anticolonial museum work by exploring two separate, but intertwined art education projects (cases) carried out in collaboration between the Art Education Programme at Aalto University, the Finnish National Gallery's Ateneum Art Museum, the Amos Rex art museum, and individuals associated with local NGOs. The chapter concludes with an emphasis on solidarity; to sensibly and ethically combat systemic discrimination supported and maintained by museums and countless educators despite of their personal and collective aims and ideals. The chapter challenges the prevailing binary divisions within museum knowledges and their inscribed hegemonic, hierarchical structures between people, objects and knowledges. As a critical stance, the authors present the need for anticolonial and co-constructed knowledges where authority is shared, and where critical knowledge as a discourse strives to move past normative ways to perceive, experience, articulate and contextualise museum objects. The notions of sensible, anticolonial museum also brings forth non-verbal, embodied knowledge and sensuous epistemic orientation: artivist solidarity.
Keywords: taidemuseot; museot; museopedagogiikka; taidekasvatus; intersektionaalisuus; solidaarisuus; queer-tutkimus